Is It Islamic Bank Really Islam? (Based on Previous Research) - Maya Permata Sari (MAMEN: Jurnal Manajemen, 2023)
One of the businesses with the fastest global growth right now is Islamic banking. The main purpose of this paper is to describe the gap between the implementation of Syariah value in Islamic banking based on previous research whose concern study is about Syariah law implementation. Islamic banks and traditional banks can be distinguished by five specific characteristics: (a) underlying principles and values; (b) offering interest-free goods and services; (c) limiting business transactions to those that adhere to Islamic law; (d) emphasizing social and developmental objectives; and (e) being subject to further inspections by the Syariah Supervisory. Using Systematic Literature Review (SLR) with the PICos method to establish the research question, the author decides to find out how far Islamic banking implementation syariah value. A systematic literature review (SLR) is a high-level objective review of a body of previously published literature that uses a clear and reproducible technique for searching, evaluating, and synthesizing it. Our analysis of the literature revealed that most Islamic banking is not purely implemented the Syariah principles in their products, services, and systems.